Self-management behavior and its influencing factors among adults with chronic obstructive pulmonary disease in Colombo, Sri Lanka: A cross-sectional study - Weerasooriya, Kanchana Warnakula Royal; Samartkit, Niphawan; Masingboon, Khemaradee; Witheethamasak, Pachanok (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Self-management behaviors are essential to take care of chronic obstructive pulmonary disease (COPD). However, data on COPD self-management practices in Sri Lankan adults is limited. Therefore, identifying the level of COPD self-management and examining its influencing factors are essential for healthcare providers to manage COPD effectively. Objectives: This research aimed to describe the level of self-management behaviors and determine whether dyspnea, perceived stress, COPD knowledge, and social support can predict self-management in adults with COPD in Colombo, Sri Lanka. Methods: A predictive correlational study was conducted, and 108 adults with mild to moderate COPD were recruited from the central chest clinic in Colombo, Sri Lanka, from March to April 2024 using a simple random sampling technique. A self-administered questionnaire was used to gather data included demographic characteristics. The other instruments used were the COPD Self-Management Scale, the Perceived Stress Scale, the COPD Knowledge Questionnaire, and the Perceived Social Support Scale. Descriptive statistics and multiple regression were used for data analysis. Results: The study showed a moderate self-management level with a mean of 3.04 ± 0.35. All variables could explain 41.7% of the variance in self-management among adults with mild to moderate COPD and COPD self-management behaviors significantly predicted by dyspnea (β = 0.212, p = 0.006), perceived stress (β = -0.195, p = 0.018), COPD knowledge (β = 0.263, p = 0.001), and perceived social support (β = 0.366, p <0.001). Conclusion: The study shows evidence that a program to intervene targeting COPD knowledge and perceived social support, in addition to reducing dyspnea and perceived stress, can be beneficial in promoting better self-management behaviors among adults with mild to moderate COPD.